Evaluation of chronic otitis media using computed tomography of temporal bone - Senniappan, Shivakumar; Chakravarthy. G., Ahil; Juvekar, Prerna (Journal of Neonatal Surgery, 2025)
Introduction: Chronic otitis media is a inflammatory condition of middle ear, which is treated by appropriate surgery. Prior to surgery to evaluate extent of disease, complications and anatomical variation is essential. Our study is to determine the reliability of HRCT temporal bone for this purpose. Methodology: Chronic otitis media patients attending ENT OPD who underwent HRCT temporal bone and treated surgically were taken in the study after obtaining informed consent with the clearance of Institutions Ethical committee. Results: HRCT exhibited excellent sensitivity and specificity in identifying different abnormalities within the temporal bone, including erosion of the scutum and malleus, mastoiditis, and mastoid abscess, achieving 100% sensitivity and specificity. Moreover, it demonstrated high sensitivity in detecting cholesteatoma across various regions of the middle ear and mastoid, with a sensitivity exceeding 80%. Nevertheless, its sensitivity varied depending on the complication, with facial canal dehiscence and tegmen erosion showing 100% specificity but lower sensitivity for other complications. Discussion: Similar results with other studies were found and has shown HRCT as a reliable investigation for preoperative evaluation. Conclusion: HRCT showed high sensitivity and specificity in identifying different abnormalities within the temporal bone. To make a more valid comparison with the conventional research, another population-based study with a longer length Interval is required.